(untitled) - Armstrong, Kelley (New York, NY, 2022)
"Its not always easy to live in the hidden town of Rockton, something Detective Casey Duncan knows firsthand. Tucked away in the Yukon wilderness, the community survives--and thrives--because the residents many secrets stay just that--secret. But what happens when these secrets start to come out? Overnight, no one is safe. Its not a question of if your secret will come out--but when. Casey and her boyfriend, Sheriff Eric Dalton, need to find the culprit while protecting those who have been thrust into the spotlight. For a place built on privacy and new beginnings, Rockton isnt handling these revelations very well. People are turning on one another, and when one of the loudest complainers turns up barely alive, its clear that their trickster is actually a murderer. The threat of exposure is reaching its breaking point, and no one knows whats going to happen next"--
Keywords: Women detectives; Fiction; Secrets; Fiction; Police; Ficiton; Thrillers (Fiction); Detective and mystery fiction